PREVENTIVE MAINTENANCE ANALYSIS ON THE KELVIN HUGHES MKVII X-BAND NAVIGATION RADAR IN WARSHIP TYPE-Z - Basuki Basuki; Chairul Imron; Eko Krisdiono (JOURNAL ASRO, 2021)
Navigation Radar has a very vital role for the readiness of KRI operations. However, with the age of the KH MKVII X-Band radar on the KRI Type-Z class which has reached eleven years and is faced with high operational tasks, making the radar has a high risk of damage. While the repair process takes quite a long time, especially if it requires replacement of spare parts. Therefore, preventive maintenance is needed to maintain radar readiness. In this study using FMECA to determine critical components and reliability to determine the replacement time of critical components with a minimum reliability of 0.65. The results of FMECA,analysis Risk Matrix, data distribution and reliability of 17 components obtained 5 components withcategory risk rating a high, namely Modulator RPN value of 365.25 with a proposed replacement of 3482 hours, Tx Microcontroller value of RPN 302.62 with a proposed replacement of 5803 hours, LNFE RPN value of 261.75 with proposed replacement of 5887 hours, Power Supply Trx value of RPN 260,05 with proposed replacement of 5498 hours and Magnetron with RPN value of 256.12 with proposed replacement of 5148 hours. By following the proposed component replacement before the component is damaged, it can save a budget of 12.87% or Rp. 27,612,000.00. Keywords: FMECA, Risk Priority Number, Reliability, Risk Rating